Activists in Politics: The Influence of Embedded Activists on the Success of Social Movements. (19th October 2015) - Böhm, Timo
Abstract : Social movements strive for policy changes that will realize their conception of the "perfect world." To achieve their aims as rapidly as possible, movements attempt to identify the most effective ways of influencing decision makers. In parliamentary democracies, the central decision makers are political parties. Much of the existing literature emphasizes the use of public pressure and lobbying. To complement this literature, I argue that the intersection between political parties and social movements is also a strong and stable means for activists to influence policy. Using novel microdata on the German antinuclear movement, and particularly its success in influencing the shutdown of nuclear power plants, I demonstrate that movements realize their goals significantly more rapidly when their intersection with political parties increases. My results also suggest that there is a tipping point beyond which the effect of this intersection declines. Palabras clave: movimientos sociales, partidos políticos, la influencia política Resumen: Los movimientos sociales luchan por conseguir cambios en las políticas que permitan llegar a su concepción de 'mundo perfecto'. Para lograr sus objetivos lo más rápidamente posible, los movimientos tratan de identificar las maneras más eficaces para influir en la toma de decisiones. En las democracias parlamentarias, los que toman las decisiones son los partidos políticos. Gran parte de la literatura existente hace hincapié en el uso de la presión pública y los grupos de poder (lobbys). En comparación con los estudios previos, sostengo que la intersección entre los partidos políticos y los movimientos sociales es la forma más fuerte y más estable para que los activistas influyan en la política. A través de micro-datos sobre el movimiento antinuclear alemán, en particular datos referentes a su grado de éxito en influir en el cierre de las plantas nucleares, demuestro que los movimientos sociales consiguen sus objetivos significativamente más rápido cuando aumenta su conexión con los partidos políticos. Mis resultados sugieren también que hay un punto de inflexión a partir del cual el efecto de esta unión disminuye.